IMPROVING STUDENT’S READING COMPREHENSION OF DESCRIPTIVE TEXT BY USING COLLABORATIVE STRATEGIC READING (CSR) TO EIGHT GRADE STUDENTS AT JUNIOR HIGH SCHOOL - Mira Febtisari; Fitrawati Fitrawati (Journal of English Language Teaching, 2017)
In this paper, the writer use a strategy known as the Collaborative Strategic Reading (CSR), which is taught in the classroom. This paper was written because there are some problems faced by the students while they are reading comprehension, which are: the students have read the low interest, low vocabulary and low critical thinking skill. Finally, students are lazy to read and reading strategies that are less good. Other factors are teachers’ less creative in selecting strategies for teaching. Collaborative Strategic Reading is a technique that teaches students to work cooperatively on a reading assignment to improve better comprehension. This strategy can maximize the development of students to think critically consisting of four phases, such as: Preview, click and clunk, Get the Gist, and Wrap Up. This paper is also contained a description of how the implementation of teaching reading by using CSR strategies. The writer hopes this strategy can help English teachers in teaching reading in an effort to improve students' reading ability.